Shared decision making bei seltenen Erkrankungen - Krause, Franziska (Ethik in der Medizin, 2019)
Definition of the problem Rare diseases pose manifold challenges to the healthcare system, e.g. how patients with a rare disease can obtain equal access to medical care and research as people with...
Gesehen am 28.08.2019